Factors influencing social and community participation of people with spinal cord injury in Karnataka, India - Heavenna Babu; Sheetal Sriraman; Suruliraj Karthikbabu; P Sophia; Senthil N S. Kumar (Wolters Kluwer Medknow Publications, 2024)
Background: Social and community participation are major indicators to assess the adequacy of treatment and rehabilitation in patients with spinal cord injury (SCI). This study examined the relationship between functional independence, level of disability, and social and community participation among people with SCI in India. Materials and Method: In this cross sectional study, 110 persons with SCI, aged 18 years and above participated in a community setting, in Karnataka, India. Spinal Cord Independence Measure Version III-self-reporting (SCIM III-SR), Craig Handicap Assessment and Reporting Technique (CHART), and WHO Disability Assessment Schedule 2.0 (WHODAS) were the clinical outcome measures. Spearman's correlation and stepwise multiple linear regression were done to determine association and identify the factors determining the community participation of people with SCI. Results: CHART physical independence had a positive correlation with SCIM self-care (R = 0.446) and SCIM mobility (r = 0.434). CHART cognitive independence (R = -0.38) and CHART mobility (R = -0.396) had a weak correlation with WHODAS. SCIM self-care and SCIM mobility (R2 = 0.34) were determinants of CHART cognitive independence. SCIM respiratory and sphincter management and SCIM self-care (R2 = 0.327) were determinants of CHART mobility. Conclusion: Self-care and mobility of people with SCI determine their ability to successfully reintegrate into the community, warranting a comprehensive community rehabilitation program.